Availability and Readability of Online Patient Information on Osteosarcoma: Assessment of Pediatric Hospital and National Cancer Institute-Designated Cancer Center (NCIDCC) Osteosarcoma Web Pages. Issue 3 (July 2020) - Young, Jason; Dee, Edward Christopher; May, Collin
Abstract : Background: Online patient information (OPI) plays an important role in pediatric orthopaedic patient/caregiver education and decision-making. We assessed the availability and readability of OPI about osteosarcoma found at pediatric hospital and U.S. National Cancer Institute-designated cancer center (NCIDCC) websites. Methods: The websites of all NCIDCCs and the top 50 pediatric hospitals identified using U.S. News & World Report were included. The names of NCIDCCs and pediatric hospitals along with the terms "osteosarcoma, " "bone sarcoma, " and "sarcoma" were entered into Google.com, and were classified according to the availability of osteosarcoma-specific web pages. Unpaid monthly visits were assessed using the Ahrefs.com Organic Traffic Score (OTS) metric. Readability was assessed using 5 validated metrics and the composite grade level (CGL), the rounded mean of the 5 metrics. Results: Of the 71 NCIDCCs and 50 pediatric hospitals, 48 (67.6%) and 18 (36.0%), respectively, did not have at least 1 web page dedicated to osteosarcoma-specific OPI. The mean OTS for all 116 NCIDCC and pediatric hospital osteosarcoma-specific web pages assessed was 177 estimated visits per month, which was less than the mean OTS for the top 10 Google.com "osteosarcoma" search results (3, 287.9; p < 0.001). The 52 NCIDCC web pages with osteosarcoma OPI (representing 23 centers) had an average CGL of 12.9, representing a readability level of at least a high school degree. The mean CGL for the 64 pediatric hospital web pages with osteosarcoma OPI (representing 32 hospitals) was 12.8, also representing readability of at least a high school degree. Only 8 (12.5%) of the 64 web pages were written at a seventh or eighth-grade level. Conclusions: Taken together, the majority of NCIDCCs and pediatric hospitals did not have a dedicated page of OPI for osteosarcoma. Of those that did, NCIDCC and pediatric hospital sites were visited much less frequently than sites visited through the most common Google.com searches. None of the osteosarcoma web pages offering OPI from NCIDCCs and pediatric hospitals met the American Medical Association readability recommendation (sixth-grade reading level). Therefore, greater effort must be made to create and direct patients and parents toward high-quality OPI of the appropriate level. Clinical Relevance: The clinical relevance of this study lies in its evaluation of OPI and its ability to impact the patient experience of clinical care.